Katharine Downie on measuring resilience in drylands of East Africa - Downie, K. (International Food Policy Research Institute, 2014)
Katharine Downie, Coordinator for the Technical Consortium for Building Resilience in the Horn of Africa, ILRI, at the side event, “Measuring and Evaluating Resilience in Drylands of East Africa”. IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info